All Days 2007
DOI: 10.2118/111420-ms
|View full text |Cite
|
Sign up to set email alerts
|

Two Phase Flow Properties of Brine-CO2 Systems in Carbonate Core: Influence of Wettability on Pc and kr

Abstract: The design of a CO2 injection project mainly depends on the results of reservoir models. Nevertheless, it is recognized that these models generally lack physico-chemical data. This issue becomes more important for storage options, such as deep saline aquifers, for which economically driven data collection and archiving have not been performed. Among these physico-chemical data, fluid/fluid and rock/fluid interactions have been long recognized to govern fluid distribution and behavior in the porous media. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The capillary displacement pressure in a tube is caused by the curved interface between the non-wetting phase (CO 2 ) and wetting phase (water). It can be described by the modified Young-Laplace equation (Chalbaud et al, 2007),…”
Section: Capillary Displacement Pressurementioning
confidence: 99%
“…The capillary displacement pressure in a tube is caused by the curved interface between the non-wetting phase (CO 2 ) and wetting phase (water). It can be described by the modified Young-Laplace equation (Chalbaud et al, 2007),…”
Section: Capillary Displacement Pressurementioning
confidence: 99%
“…For the CO 2 /brine system, surface tension and wettability measurements as a function of the temperature have been reported recently (Chalbaud et al, 2009(Chalbaud et al, , 2010.…”
Section: Quantitative Interpretation -Two Phase Flow Immiscible Displmentioning
confidence: 99%
“…The wettability of aqueous and nonaqueous fluids on solid surfaces has a well-established impact on the transport of multiple phases through porous media . The specific case of a hydrated mineral surface in contact with a hydrophobic nonaqueous phase fluid is relevant to a number of applications related to energy and/or the environment such as geologic carbon sequestration (GCS), enhanced oil recovery, and hydraulic fracturing of shales. , At the surface, most minerals contain hydroxyl functional groups (e.g., Al–OH and Si–OH) in equilibrium with the aqueous phase so that under conditions in which nonaqueous species (e.g., CO 2 , oil, or CH 4 ) contact the surface, it would be expected to maintain its water-wetting characteristics . Most work has suggested that differences in the solution chemistry (e.g., pH, ionic strength) and the mineral composition at the pore surface (e.g., quartz, kaolinite, silica, calcite) could lead to minor differences in wettability. , These changes would manifest on macro-scale flow properties like capillary pressure and residual saturation but are unlikely to change transport behavior dramatically …”
Section: Introductionmentioning
confidence: 99%